Architectonic features of the novel «Azazel» by Yusuf Zeidan - Бессараб, Олександр Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The architectonic features of the novel «Azazel’» by Yusuf Zeidan are defined in the article. Much attention is given to the architectonic elements used by the author in the structure of the novel on the religious subject matter. For analysis the classical differentiation of the text composition is used. These are external (architectonics) and internal (content) compositions. Two types of text segmentation were examined: extensional and pragmatic type which coincides with the external composition and context and variable one. Their combination influences on the work composition through the using of author’s language, descriptions, deep thoughts and clarifying of the main character’s point of view. Cohesion and coherence are defined as the key features of architectonics and relatedness of the text.